Antisense mRNA-Mediated Bacteriophage Resistance in Lactococcus lactis subsp. lactis - Kim, Sung Guk (1991)
Resistance to a broad class of isometric bacteriophages that infect strains of Lactococcus lactis has been engineered into a dairy starter by expression of antisense mRNA targeted against a conserved bacteriophage gene. Maximum protection is obtained only when the entire 1,654-bp coding sequence for a 51-kDa protein is positioned in the antisense orientation with respect to a promoter sequence that functions in L. lactis subsp. lactis. Expression of the antisense mRNA results in more than 99% reduction of the total number of PFU. Plaques that do form are characterized by their relatively small size and irregular shape. A variety of truncated genes, including the open reading frame expressed in the sense orientation, fail to provide any significant measure of resistance as compared with that of the intact open reading frame. Southern hybridization with probes specific for the conserved region reveal that the [ill] plasmid constructs are maintained despite the presence of a large complement of other indigenous plasmids. Strains harboring the antisense mRNA plasmid construct grow and produce acid at a rate equivalent to that of the host strain alone, suggesting that antisense expression is not deleterious to normal cellular metabolism.